Focused ultrasound-mediated blood–brain barrier opening is safe and feasible with moderately hypofractionated radiotherapy for brainstem diffuse midline glioma - Masih Tazhibi; Nicholas McQuillan; Hong-Jian Wei; Matthew Gallitto; Ethan Bendau; Andrea Webster Carrion; Xander Berg; Danae Kokossis; Xu Zhang; Zhiguo Zhang; Chia-Ing Jan; Akiva Mintz; et al. (Journal of Translational Medicine, 2024)
Abstract Background Diffuse midline glioma (DMG) is a pediatric tumor with dismal prognosis. Systemic strategies have been unsuccessful and radiotherapy (RT) remains the standard-of-care. A central impediment to treatment is the blood–brain barrier (BBB), which precludes drug delivery to the central nervous system (CNS). Focused ultrasound (FUS) with microbubbles can transiently and non-invasively disrupt the BBB to enhance drug delivery. This study aimed to determine the feasibility of brainstem FUS in combination with clinical doses of RT. We hypothesized that FUS-mediated BBB-opening (BBBO) is safe and feasible with 39 Gy RT. Methods To establish a safety timeline, we administered FUS to the brainstem of non-tumor bearing mice concurrent with or adjuvant to RT; our findings were validated in a syngeneic brainstem murine model of DMG receiving repeated sonication concurrent with RT. The brainstems of male B6 (Cg)-Tyrc-2J/J albino mice were intracranially injected with mouse DMG cells (PDGFB+, H3.3K27M, p53−/−). A clinical RT dose of 39 Gy in 13 fractions (39 Gy/13fx) was delivered using the Small Animal Radiation Research Platform (SARRP) or XRAD-320 irradiator. FUS was administered via a 0.5 MHz transducer, with BBBO and tumor volume monitored by magnetic resonance imaging (MRI). Results FUS-mediated BBBO did not affect cardiorespiratory rate, motor function, or tissue integrity in non-tumor bearing mice receiving RT. Tumor-bearing mice tolerated repeated brainstem BBBO concurrent with RT. 39 Gy/13fx offered local control, though disease progression occurred 3–4 weeks post-RT. Conclusion Repeated FUS-mediated BBBO is safe and feasible concurrent with RT. In our syngeneic DMG murine model, progression occurs, serving as an ideal model for future combination testing with RT and FUS-mediated drug delivery.